2015
DOI: 10.1007/s00253-015-7079-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of malate transporter in lipid accumulation of oleaginous fungus Mucor circinelloides

Abstract: Fatty acid biosynthesis in oleaginous fungi requires the supply of reducing power, NADPH, and the precursor of fatty acids, acetyl-CoA, which is generated in the cytosol being produced by ATP: citrate lyase which requires citrate to be, transported from the mitochondrion by the citrate/malate/pyruvate transporter. This transporter, which is within the mitochondrial membrane, transports cytosolic malate into the mitochondrion in exchange for mitochondrial citrate moving into the cytosol (Fig. 1). The role of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 27 publications
1
45
1
Order By: Relevance
“…Previously, the malate transporter ( mt ) gene was overexpressed or knocked out in M. circinelloides to construct recombinant strains, which are as follows: MU522 ( mt -knockout, CCTCC M 2015552), MU241 (wild-type, as the control) and Mc-MT ( mt -overexpression, CCTCC M 2015551). The transformants of mt -overexpressing gene were named Mc-MT-1 and Mc-MT-2, respectively [16]. These engineered strains were respectively inoculated in high nitrogen (HN) and low nitrogen (LN) modified K & R medium with glucose as the sole carbon source.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, the malate transporter ( mt ) gene was overexpressed or knocked out in M. circinelloides to construct recombinant strains, which are as follows: MU522 ( mt -knockout, CCTCC M 2015552), MU241 (wild-type, as the control) and Mc-MT ( mt -overexpression, CCTCC M 2015551). The transformants of mt -overexpressing gene were named Mc-MT-1 and Mc-MT-2, respectively [16]. These engineered strains were respectively inoculated in high nitrogen (HN) and low nitrogen (LN) modified K & R medium with glucose as the sole carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the genomic data search and sequences analysis of M. circinelloides CBS277.49, a gene (ID180302) encoding malate transporter was found in NCBI and named mt . Both null mutant (Mu522) and overexpressing strains (Mc-MT-1 and Mc-MT-2) of this gene were previously constructed in our laboratory [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the genomic data of M. alpina , this study found only one gene encoding for D15D (Genebank accession number KF433065), which is 1212 bp long. For overexpression of the target gene, the coding region of D15D was cloned into the M. circinelloides expression vector pMAT1552, which contained the strong zrt1 promoter and flanking sequence of carRP locus to allow integration of the whole over-expressing construction by homologous recombination [26]. Integration in carRP locus produced white colonies, which were easily distinguishable from yellow transformants that did not integrate the D15D gene.…”
Section: Resultsmentioning
confidence: 99%
“…It is hypothesis that, the A.niger didn't shows good intensity of key isoform (E), the isoform that related to lipid biosynthesis pathway in lipid accumulation with its relations on gene expression [27,28]…”
Section: Activity Of Key Enzymes Duringmentioning
confidence: 99%